2009
DOI: 10.1242/jcs.052373
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor NHR-25 cooperates with the Wnt/β-catenin asymmetry pathway to control differentiation of the T seam cell inC. elegans

Abstract: Asymmetric cell divisions produce daughter cells with distinct developmental fates, therefore representing a key mechanism of tissue and organ differentiation during animal development (Betschinger and Knoblich, 2004;Roegiers and Jan, 2004; Gönczy, 2008). Cell commitment to a particular fate depends on establishment of a polarity axis, orientation of mitotic spindle along this axis and asymmetric segregation of cell-fate determinants. These processes are ensured by precise spatial and temporal cellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…For example, the larval asymmetric division of the T cell, the most posterior of the seam cells, which differentiate under the control of let-7 at the adult stage, is regulated by SWI/SNF, together with Wnt signaling (Sawa et al 2000), the Hox protein NOB-1/Abd, and cofactors PSA-3/Meis and CEH-20/Pbx (Arata et al 2006), and the nuclear hormone receptor encoded by nhr-25 (Hajduskova et al 2009), itself a target of let-7 ). SOMI-1 may promote alterations in chromatin structure, mediated by a PBAF-like complex, that occur in response to expression of mir-84 and let-7 and oppose the activity of larval fate-promoting factors.…”
Section: Chromatin-remodeling Complexes and Differentiationmentioning
confidence: 99%
“…For example, the larval asymmetric division of the T cell, the most posterior of the seam cells, which differentiate under the control of let-7 at the adult stage, is regulated by SWI/SNF, together with Wnt signaling (Sawa et al 2000), the Hox protein NOB-1/Abd, and cofactors PSA-3/Meis and CEH-20/Pbx (Arata et al 2006), and the nuclear hormone receptor encoded by nhr-25 (Hajduskova et al 2009), itself a target of let-7 ). SOMI-1 may promote alterations in chromatin structure, mediated by a PBAF-like complex, that occur in response to expression of mir-84 and let-7 and oppose the activity of larval fate-promoting factors.…”
Section: Chromatin-remodeling Complexes and Differentiationmentioning
confidence: 99%
“…The protein was also involved in controlling fat uptake and storage by regulating acyl-CoA synthase-3 activities (13). In addition, NHR-25 cooperates with the Wnt signaling pathway to control fate differentiation of T seam cells and somatic gonad (14). Despite dramatic expansion of the NHR family, genome-wide binding targets have not been determined for any member of the family in C. elegans.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that loss of nhr-25 function causes various phenotypes throughout development, such as defects on embryogenesis, differentiation of larval epidermis, molting, distal tip cell/anchor cell formation, and cell-cell fusion in vulval morphogenesis (Asahina et al, 2000; Asahina et al, 2006; Chen et al, 2004; Gissendanner and Sluder, 2000; Hajduskova et al, 2009; Silhankova et al, 2005). These observed phenotypes are the result of earlier or very severe knock-down and may have masked later or alternative functions.…”
Section: Discussionmentioning
confidence: 99%
“…nhr-25 belongs to the evolutionarily conserved nuclear receptor NR5A subfamily, including insect fushi tarazu-factor 1 (FTZ-F1) , mammalian steroidogenic factor 1 ( SF-1 ) and liver receptor homolog 1 ( LRH-1 ) (Asahina et al, 2000; Gissendanner and Sluder, 2000). Previous studies have shown that nhr-25 is necessary for a variety of developmental events, such as embryogenesis, hypodermal differentiation, exoskeleton production, vulval formation, and gonadal morphogenesis (Asahina et al, 2000; Asahina et al, 2006; Chen et al, 2004; Gissendanner and Sluder, 2000; Hajduskova et al, 2009; Silhankova et al, 2005). nhr-25 is also a downstream target of let-7 and other heterochronic genes involved in the cessation of molting (Hayes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%